2005
DOI: 10.1016/j.compedu.2004.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Using a shared workspace and wireless laptops to improve collaborative project learning in an engineering design class

Abstract: Two different technologies, groupware (a shared workspace) and shared wireless laptop computers, were implemented in a project design class in a civil engineering course. The research interest was in the way these technologies supported resource sharing within and across project groups and in the forms of group collaboration that resulted. The initiative was evaluated using both qualitative (e.g. pyramid discussion) and quantitative methods (e.g. survey, logs of usage). The results showed that these technologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 15 publications
3
21
0
Order By: Relevance
“…As shown elsewhere (Nicol & Macleod, 2004; Sikkel et al , 2002), the studies reported here show that a shared workspace (TikiWiki, LauLima) helped support collaborative learning. The students reported the value of being able to access and contribute to the development of resources at any time and from any location.…”
Section: Educational Contextsupporting
confidence: 77%
“…As shown elsewhere (Nicol & Macleod, 2004; Sikkel et al , 2002), the studies reported here show that a shared workspace (TikiWiki, LauLima) helped support collaborative learning. The students reported the value of being able to access and contribute to the development of resources at any time and from any location.…”
Section: Educational Contextsupporting
confidence: 77%
“…It is known that the pedagogical use of ICTs requires careful planning, and best practices are often found through long-term development and repeated implementations (Jonassen et al, 2005;Nicol & McLeod, 2005). At present however, pedagogical planning seems to start from planning a single course's activities and interactions, whereas we suggest that strategic and long-term planning should also consider the multi-level and complex domestication process that precedes actual courses and learning processes.…”
Section: Discussionmentioning
confidence: 99%
“…Many keys to pedagogically successful use of ICTs have been identified in previous research, which has also yielded practical recommendations. The most mentioned include longterm strategic pedagogical planning of implementing technology in education (Jonassen, Lee, Yang & Laffey, 2005;Nicol & McLeod, 2005); high quality of faculty utilisation of the technology for teaching and students having choices as regards technology (Demb, Erickson & Hawkins-Wilding, 2004); engagement of students in active learning and problem solving through ICTs (Barak, Lipson & Lerman, 2006); and support for the development of network based communities and feelings of trust (McInnerney & Roberts, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Gagn e's early work in the 1940s and 1950s was based on assumptions from behavioral psychology, where instruction is the reinforcement of appropriate learner responses to stimulus situations set up by the teacher. Nicol and MacLeod [5] investigated two different technologies: groupware and shared laptops with wireless access in a project design class in civil engineering course. In this view instruction is seen as organizing and providing sets of information and activities that guide, support, and augment students' internal mental processes.…”
Section: Introductionmentioning
confidence: 99%